2014
DOI: 10.1007/s10529-014-1656-5
|View full text |Cite
|
Sign up to set email alerts
|

Technology developments in biological tools for targeted genome surgery

Abstract: Different biological tools for targeted genome engineering have recently appeared and these include tools like meganucleases, zinc-finger nucleases and newer technologies including TALENs and CRISPR/Cas systems. transcription activator-like effector nucleases (TALENs) have greatly improved genome editing efficiency by making site-specific DNA double-strand breaks. Several studies have shown the prominence of TALENs in comparison to the meganucleases and zinc-finger nucleases. The most important feature of TALE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…To avoid or prevent significant risks of off-target mutations, we chose TALENs to achieve mutagenesis instead of CRISPR. Even though CRISPR has emerged recently as a potentially facile and efficient alternative to ZFNs and TALENs to induce targeted genetic alterations, CRISPR does not have better specificity than TALENs or ZFNs [ 17 , 26 ]. Meanwhile previous studies have shown that low efficacy and minor off-target mutations may exist in TALEN-induced animals [ 22 , 23 , 28 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid or prevent significant risks of off-target mutations, we chose TALENs to achieve mutagenesis instead of CRISPR. Even though CRISPR has emerged recently as a potentially facile and efficient alternative to ZFNs and TALENs to induce targeted genetic alterations, CRISPR does not have better specificity than TALENs or ZFNs [ 17 , 26 ]. Meanwhile previous studies have shown that low efficacy and minor off-target mutations may exist in TALEN-induced animals [ 22 , 23 , 28 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile previous studies have shown that low efficacy and minor off-target mutations may exist in TALEN-induced animals [ 22 , 23 , 28 31 ]. However, TALENs still provides a valuable option, thanks to its relatively high specificity [ 26 ]. Off-target analysis of the cloned goats revealed that no off-target sequences were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Other advantages of using phiC31 integrase include non-viral delivery, sustainable transgene expression, and functions in species like bacteria, yeast, plants, frogs, chickens, mice, rats, pigs, cows, and humans. [2,73] However, potential sites of phiC31-based genome editing are limited. In human genome, of the 106 mapped integration sites of phiC31, ~ 39% are within coding genes and ~ 61% are in the intergenic regions.…”
Section: Meganucleasementioning
confidence: 99%
“…1 ). 8 , 9 , 10 The deletions or excisions of DNA induced by CRISPR in order to restore ORF is a new and encouraging approach in treating patients caused by deletion and duplication mutations that disrupt ORF. Also, the precise correction of the mutation through CRISPR-induced homologous directed repair (HDR) is another hallmark that brings by CRISPR/Cas9 technology for the treatment of DMD.…”
Section: Introductionmentioning
confidence: 99%